Problems and perspectives of European transport policy - Christian Woelker (Intereconomics, 1976)
The article offers a survey of the different international bodies concerned with European transport policy, their relative competencies and special problems. Furthermore, some fundamental guidelines are provided which should be followed in order to achieve more efficiency in traffic.
Keywords: 330; Transportation